Simulating potential impacts of solar MajiPump on the economy and nutrition of smallholder farmers in sub-humid Ethiopia - Bizimana, J.-C.; Yalew, B. B.; Assefa, T. T.; Belay, S. A.; Degu, Y. M.; Mabhaudhi, Tafadzwanashe; Reyes, M.R.; Prasad, P. V. V.; Tilahun, Seifu A. (MDPI, 2023)
Irrigation is widely considered a potential means to improve agricultural productivity, nutrition, and income, as farmers can carry out farming and production year-round. However, the feasibility of irrigation technologies is highly dependent on the long-term economic return farmers achieve. Solar-based irrigation could address the challenges of underinvestment in irrigation within Africa. Evidence on the economic viability of the adopted solar pumps such as MajiPump is very scant and focused on ex post evaluation. This study evaluated the income and nutritional feasibility of solar-powered irrigation using the MajiPump in sub-humid Ethiopian highlands using the farm simulation (FARMSIM) model and compared it with the manual pulley system. Results from the FARMSIM model show that farmers’ adoption of Maji solar pump technology to grow vegetables is economically feasible with financial support such as credit or loan for initial and capital investment to acquire the pump. The average profit under the solar MajiPump, drip irrigation, and conservation agriculture was 3.6 times higher than that of the baseline scenario. While the pulley technology provides the same amount of irrigation water to grow vegetables, its feasibility is limited due to high labor costs and time, estimated to be more than seven times the baseline. The simulation results show that the alternative scenarios’ nutrition level has improved relative to other scenarios and met the minimum daily average nutrition requirement level for proteins, iron, and vitamin A but fell short in fat, calcium, and calories. The results suggest that farmers who adopt improved small-scale irrigation technologies (solar MajiPump and drip system) have a higher potential to increase production and income from irrigated crops and improve their nutrition if part of the income generated is used to purchase supplemental food for their nutrition.